NEFROPROTECTOR EFFECT OF CURCUMIN (CURCUMA LONGA) AND VITAMIN E (α-TOCOPHEROL) IN WISTAR STRAIN RATS AFTER CISPLATIN TREATMENT - Sirait, Binsar Marshall Maranatha; Wahjoe Djatisoesanto; Soetojo (Indonesian Urological Association, 2021)
Objective: To analyze the effect of curcumin and vitamin E on kidney function and inflammatory response of Wistar strain rats that received cisplatin. Material & Methods: An experimental laboratory study with a post-test only control design, using male Wistar strain rats (Rattus norwegicus). Rats were randomized using the simple randomized sampling method. Samples were treated with cisplatin 5 mg/kg (positive control group), vitamin E 100 mg/kg, curcumin 100 mg/kg body, and a combination of both (treatment group), to evaluate its effect on and kidney function and inflammatory response as measured by tumor necrosis factor-α (TNF-α), blood urea nitrogen (BUN) and serum creatinine. Results: There were differences in TNF-α levels in the positive control group (cisplatin 5 mg/kg) against each treatment group (p<0.05). Further analysis showed that there was a significant difference between the treatment group that received vitamin E and curcumin from the treatment group that received a combination of both (P<0.05). In addition, there were differences in BUN and serum creatinine levels in the positive control group (cisplatin 5 mg/kg) against each treatment group (p<0.05). However, there was no significant difference in BUN levels in the treatment group that received vitamin E with the treatment group that received curcumin or a combination of both (p>0.05). No differences were found in serum creatinine levels between treatment groups receiving vitamin E, curcumin, or a combination of both. Conclusion: Vitamin E 100 mg/kg, curcumin 100 mg/kg, and the combination of both have a nephroprotector feature in Wistar rats exposed to cisplatin.